A proposed Islamic Performance Management Model (IPMM): towards more productive employees with better quality of work life / Noor Liza Adnan ...[et al.] - Adnan, Noor Liza; Wan Jusoh, Wan Noor Hazlina; Muda, Rokiah; Yusoff, Rohana (Universiti Teknologi MARA, 2021)
This paper introduces a conceptual idea of Performance Management (PM) system named Islamic Performance Management Model (IPMM). Based wholly on material aspects, the current system is incomplete and imbalanced. IPMM considers both material and spiritual aspects plus efforts exerted by employees. Such measurement will self-regulate employees to view work as an 'ibadah' which promotes self-supervision leading to highly ethical workforce. Articles on Islamic management and related parts of al-Quran and Sunnah provide a rich source of knowledge to achieve the paper's objective. Findings from the review are used to propose IPMM which starts with an Islamic leadership who creates Islamic work culture and apply the Islamic performance appraisal. IPMM develops employees who are in harmony with their colleagues and simultaneously in closer relationship with their Creator. This study contributes to new knowledge on integrating effort with outcomes in appraisal that contribute to productive workers with better quality of work life.